(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
From Artistic Practice as Research and Performance Philosophy, the question is how the performing body constructs, reconstructs and changes meanings of diverse phenomena, which expands understanding of movement and gesture as a philosophical exercise and related to holistic health dimensions. I share works in which beings move while generating self-knowledge, energetic and spiritualized power related to quality of life. The Performance “Salamandra” (2018) and the artistic exchange project “Salamandra” (2020) were carried out in times of illness, pain, affliction. Reflections complexize theoretical-practical connections to broaden thoughts about healing, science, reality, body, performance, philosophy, cognition, imagination and art.